Peran Beauty Influencer Dalam Meningkatkan Minat Beli Produk Make Up Pada Generasi Z - Indah Lestari, Novia; Ramadani, Mery; Noor Syrah, Anniba; Anggreini, Stevany (Universitas Serang Raya, 2023)
In recent years, the development of commercial communications and live broadcast events on television has attracted a lot of attention from the public, especially the younger generation. Is a Trend in today’s digital world across various social media platforms, creating an opportunity for brands to market through social media influencers, many artists or athletes getting involved with the product and delivering their reviews so that many target audiences. We call beauty influencers. Currently, generation Z will tend to look at reviews from beauty influencers before they buy a product. This research aims to see the effect of beauty influencers on customer purchase intention in cosmetic products. This research on Generation Z. The sample was 100 respondents using purposive sampling. The data will be processed using regression. The results show that the role of beauty influencers can increase the purchase intentions of Generation Z partially or simultaneously and influences 87.6% and the remaining 12.4% is influenced by other variables not examined in this research. Keywords : beauty influencer, purchase intention, gen z